O32 Asymptomatic neurosyphilis is unlikely in hiv infected patients after treatment for early syphilis with benzathine penicillin g. (18th May 2015) - Tomkins, Andrew; Ahmad, Shazaad; Cousins, Darren E; Vilar, Francisco Javier; Higgins, Stephen P
Abstract : Background/introduction: Benzathine penicillin G (BPG) does not cross the blood-brain barrier. Some experts believe that BPG may be ineffective when treating patients co-infected with HIV and syphilis. Aim(s)/objectives: To establish the risk of asymptomatic neurosyphilis (ANS) after treatment of early syphilis in HIV positive patients with single dose BPG. Methods: HIV patients with early syphilis were offered a post-treatment lumbar puncture if their CD4 count was <350 and/or their serum RPR >16. Patients with clinical neurosyphilis were excluded. ANS was defined as a positive CSF RPR, or CSF white blood cells >20/mm 3 plus CSF TPPA >1:320. Results: 64 patients participated (median CD4 417/mm 3, range 84–1100). 50 of the patients were treated with single dose BPG. Only one patient had ANS (prevalence 1.56% 95 CI 0.04–8.4) with CSF RPR negative, CSF TPPA 1:1280 and lymphocytes 45/mm 3 . Two patients had a pleocytosis (50 and 22 white cells/mm 3 respectively) with negative CSF RPR and CSF TPPA and thus did not meet diagnostic criteria for ANS per protocol. Discussion/conclusion: Our study suggests that single dose BPG is effective treatment for early syphilis in HIV co-infected patients. We will present more data to support this conclusion.